Public Trading and Private Incentives: - Faure-Grimaud, Antoine; Gromb, Denis (Review of Financial Studies, 2004)
This article studies the link between public trading and the activity of a firm's large shareholder who can affect firm value. Public trading results in the formation of a stock price that is informative about the large shareholder's activity. This increases the latter's incentives to engage in value-increasing activities. Indeed, if he has to liquidate part of his stake before the effect of his activity is publicly observed, a more informative price rewards him for his activity. Implications are derived for the decision to go public, capital structure, and security design.